2021
DOI: 10.3389/fgene.2020.627007
|View full text |Cite
|
Sign up to set email alerts
|

Human Ubiquitin-Specific Peptidase 18 Is Regulated by microRNAs via the 3'Untranslated Region, A Sequence Duplicated in Long Intergenic Non-coding RNA Genes Residing in chr22q11.21

Abstract: Ubiquitin-specific peptidase 18 (USP18) acts as gatekeeper of type I interferon (IFN) responses by binding to the IFN receptor subunit IFNAR2 and preventing activation of the downstream JAK/STAT pathway. In any given cell type, the level of USP18 is a key determinant of the output of IFN-stimulated transcripts. How the baseline level of USP18 is finely tuned in different cell types remains ill defined. Here, we identified microRNAs (miRNAs) that efficiently target USP18 through binding to the 3’untranslated re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…At least one other known transcript, PTENJ2 shows some analogous properties. The Rubino et al (2021) study also adds to the multifaceted properties of 3'UTRs, properties that other investigators have previously described. For example, Mercer et al (2011) and Kocabas et al (2015) showed that many 3'UTR sequences are independently expressed in the absence of protein coding sequences and that their expression is regulated during development.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…At least one other known transcript, PTENJ2 shows some analogous properties. The Rubino et al (2021) study also adds to the multifaceted properties of 3'UTRs, properties that other investigators have previously described. For example, Mercer et al (2011) and Kocabas et al (2015) showed that many 3'UTR sequences are independently expressed in the absence of protein coding sequences and that their expression is regulated during development.…”
Section: Discussionmentioning
confidence: 81%
“…Although the evolutionary history of the formation of linc-UR-B1 is incomplete, the work of Rubino et al (2021) significantly advances our knowledge of gene birth by showing how linc-UR-B1 was created in humans. And there is beauty in the simplicity of this process-insertion of a small functional unit close to the end of an existing gene, utilizing the existing transcriptional apparatus and setting in place specific regulatory mechanisms for expression of this new gene in specific cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using the miRNA as a guide, the RISC complex mediates the binding of the miRNA to the target mRNA, which results in gene silencing; a fully complementary pairing between the miRNA and the mRNA target results, indeed, in the cleavage of mRNA target. On the other side, the presence of some mismatches inhibits the translation by repressing the initial ribosome binding to the mRNA or the ribosome drop off [57][58][59].…”
Section: Biological Moleculesmentioning
confidence: 99%